DETERMINATION OF ABSORBED DOSES FROM VARIOUS RADIOGRAPHICS TECHNIQUES REQUIRED FOR DENTAL IMPLANTS - Ardakani, Fatemeh Ezoddini; Kaviyani-arani, Farzaneh; Mohammadi, Zahed (Archives of Oral Research, 2005)
The diagnostic and treatment benefits of various radiographic techniques, including those used routinely for dental implants, need to be evaluated against the complications and exposure risks involved. The aims of this study were to measure the amount of ionizing radiation absorbed by various critical tissues of the body in order to determine the risks of a radiographic procedure and to compare the amount of radiation absorbed by various tissues during radiographic procedures for dental implants. This in vitro study was performed on a humanlike X-ray phantom head using lithium thermo-luminescent dosimeters. The amount of radiation absorbed by critical tissues was more during the generation of a CT scan as compared to the use of linear tomography. The absorbed dose using these two techniques was more than when panoramic radiography was used. Organs defined as critical in this study were the eyes, thyroid glands, salivary glands, brain, bone marrow and skin. The amount of radiation absorbed by the thyroid gland during a mandibular CT scan was relatively high and therefore the use of a protective collar is recommended. The amount of radiation absorption in the parotid glands was more than the other two major salivary glands and also more than all other critical organs during a mandibular CT scan, an anterior and posterior linear tomographic survey or while taking a panoramic radiograph. The maximum amount of absorption in the parotid gland was in the maxilla CT, insignificant in relation to 10 grays, the dose resulting in acute inflammation of the gland. The maximum amount of radiation absorbed in the skin was during a mandibular CT scan which was lower than the dose resulting in erythema. The maximum amount of radiation absorbed was in during a mandibular CT scan.